2021
DOI: 10.3390/nu13030942
|View full text |Cite
|
Sign up to set email alerts
|

Current Management of Hyperkalemia in Non-Dialysis CKD: Longitudinal Study of Patients Receiving Stable Nephrology Care

Abstract: Background: No study has explored the limitations of current long-term management of hyperkalemia (HK) in outpatient CKD clinics. Methods: We evaluated the association between current therapeutic options and control of serum K (sK) during 12-month follow up in ND-CKD patients stratified in four groups by HK (sK ≥ 5.0 mEq/L) at baseline and month 12: Absent (no-no), Resolving (yes-no), New Onset (no-yes), Persistent (yes-yes). Results: We studied 562 patients (age 66.2 ± 14.5 y; 61% males; eGFR 39.8 ± 21.8 mL/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Additionally, Kalemic control is further compounded by extensive use of the renin–angiotensin–aldosterone system inhibitor (RAASI) therapy in CKD patients [ 77 ]. Development of hyperkalemia in CKD patients requires lowering the dose or discontinuation of the RAASI therapy to protect patients from developing cardiovascular events and end stage kidney disease.…”
Section: Medical Nutrition Therapymentioning
confidence: 99%
“…Additionally, Kalemic control is further compounded by extensive use of the renin–angiotensin–aldosterone system inhibitor (RAASI) therapy in CKD patients [ 77 ]. Development of hyperkalemia in CKD patients requires lowering the dose or discontinuation of the RAASI therapy to protect patients from developing cardiovascular events and end stage kidney disease.…”
Section: Medical Nutrition Therapymentioning
confidence: 99%
“…Studies in patients with CKD have shown a remarkable frequency in hyperkalemia in advanced CKD stages, hyporreninemic hypoaldosteronic diabetic patients, renal transplantation (RT), and patients with RAAS inhibition (4,6). Available information shows prevalence percentages ranging from 5 to 20% depending on the stage of CKD (13).…”
Section: Hyperkalemia In Patients With Ckd Non-dialysismentioning
confidence: 99%
“…Compensatory mechanisms may help improving tolerance to hyperkalemia in patients with CKD and a J-shaped correlation was found between serum potassium and overall mortality risk in non-dialysis patients (16). Moreover, new onset or persistence of mild-to-moderate hyperkalemia (potassium 5.0-6.0 mmol/L) during 12 months of observation significantly increased by 30% the risk of End Stage Renal Disease (ESRD) (4,17,18). It has been suggested that CKD patients adapt to elevated potassium concentrations through modifications in gastrointestinal secretions which may favor intracellular potassium storage, or by increasing insulinmediated intracellular potassium uptake in splanchnic and peripheral muscle tissues (19).…”
Section: Hyperkalemia In Patients With Ckd Non-dialysismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a relationship between potassium intake and serum K + has never been demonstrated. Indeed, the studies evaluating potassium intake by urinary potassium excretion or food frequency questionnaire have shown a weak correlation between potassium intake and serum K + concentrations in patients with non-dialytic CKD (r = 0.05) [ 41 ] and ESKD [ 25 , 42 , 43 , 44 ]. This poor correlation between serum and potassium intake is likely due to an increase in gastrointestinal excretion and intracellular redistribution.…”
Section: The Dilemma Of Nutritional Approach In Chronic Kidney Diseas...mentioning
confidence: 99%